A Measure of Comprehensive Airman Fitness: Construct Validation and Invariance Across Air Force Service Components. (2nd April 2016) - Bowen, Gary L.; Jensen, Todd M.; Martin, James A.
ABSTRACT: This article addresses the construct validity of an online assessment measure intended to reflect the biopsychosocial and spiritual fitness of U.S. Air Force (AF) members, defined as Comprehensive Airman Fitness. The analysis presented examines the extent to which this measure and the associated validation model are invariant across three AF components: active duty personnel, members of the Air National Guard/AF Reserve, and AF civilian employees. Our results indicate that total fitness (i.e., second-order factor), its four subcomponents (i.e., first-order factors), and the resiliency construct associated with role performance are invariant across service components at the configural, metric, and scalar measurement levels. Further, the strong positive association between total fitness and resiliency is statistically indistinguishable across all AF components. Limitations and implications are discussed.